The sorcerer's apprentice [video recording] (Pasig City : Viva Video Inc, 2010)
Magic is everywhere in Disney's The Sorcerer's Apprentice - the fun family adventure from the creators of National treasure. Balthazar Blake ( Nicolas Cage) is a modern-day sorcerer with his hands full defending Manhattan against dark forces. When a seemingly average kid shows hidden potential. Balthazar takes his reluctant recruit on a crash course in the art and science of magic to become the ultimate sorcerer's apprentice.
Keywords: Imaginary powers; Magic